Real-world treatment patterns and associated progression-free survival in relapsed/refractory multiple myeloma among US community oncology practices. Issue 7 (2nd July 2016) - Jagannath, Sundar; Roy, Anuja; Kish, Jonathan; Lunacsek, Orsolya; Globe, Denise; Eaddy, Michael; Kuriakose, Emil T.; Willey, Joanne; Butler-Bird, Stephanie; Siegel, David
ABSTRACT: Background : Evidence supporting optimal treatment sequencing in relapsed/refractory multiple myeloma (RRMM) patients requiring multiple therapy lines is lacking. Methods : Using retrospective chart data, this study describes real-world RRMM treatment patterns and related progression-free survival (PFS) in US community oncology clinics. Results : Bortezomib ± a non-immunomodulatory drug (IMiD), lenalidomide ± a non-proteasome inhibitor (PI), bortezomib + an IMiD were the most commonly used regimens in early lines of therapy. Median PFS was similar in 1 st (11.1 months) and 2 nd line (10.5) and decreased in lines 3 through 5 (3 rd : 7.9; 4 th : 7.2, 5 th : 5.4). Longest PFS (12.5 months) in first line was with bortezomib + ImiD; longest PFS in second line was with lenalidomide ± a non-PI was (13.2 months). Conclusions : Re-treatment with bortezomib was common; novel agents were reserved for later therapy lines. Overall, the observed PFS associated with real-world treatment sequences were shorter than those reported in clinical trials.